Resources for innovative learning of anatomy and foot ossification: Graphic design and virtual reality - Ana Cristina Moreno‐Marin; Manuel Pardo Rios; Eva Lopezosa‐Reca; Cristina Molina García; Salvador Díaz‐Miguel; Beatriz Gómez‐Martín; Paula Cobos‐Moreno (Journal of Foot and Ankle Research)
Abstract Introduction This study addresses the ossification process of the foot, a topic of great relevance within podiatry courses. Understanding the chronology of foot bone formation is essential for evaluating pathological processes and establishing appropriate therapeutic actions to improve patient quality of life. The main objectives of this work are to understand the ossification process of the foot bones and to propose an appropriate didactic methodology for effective learning of this process. Materials and Methods The individual ossification sequences of the foot bones were established and virtually recreated to make these processes more didactic and usable as teaching aids. The literature search was conducted using the PRISMA statement, focusing on terms, such as “bone ossification,” “foot,” and “bone development,” and included relevant studies from medical databases. Results Updating the ossification ages and providing previously unavailable visual teaching material offers a useful tool for improving the teaching of this subject. It was found that, in general, the tarsal bones show significant differences in ossification ages between sexes, with later and slower ossification in males. These differences are statistically analyzed and presented in detailed comparative tables. Conclusions The use of innovative teaching tools, such as virtual anatomical models, helps students to better understand the ossification process of foot bones. Implementing these tools in the podiatry curriculum not only facilitates knowledge acquisition but also enhances the quality of teaching and, consequently, the future clinical practice of students.